Intelligent systems design and applications : 16th International Conference on Intelligent Systems Design and Applications (ISDA 2016) held in Porto, Portugal, December 16-18, 2016 - Madureira, Ana; Abraham, Ajith, 1968-; Gamboa, Dorabela; Novais, Paulo (Springer, 2017)
This book comprises selected papers from the 16th International Conference on Intelligent Systems Design and Applications (ISDA?16), which was held in Porto, Portugal from December 1 to16, 2016. ISDA 2016 was jointly organized by the Portugual-based Instituto Superior de Engenharia do Porto and the US-based Machine Intelligence Research Labs (MIR Labs) to serve as a forum for the dissemination of state-of-the-art research and development of intelligent systems, intelligent technologies, and applications. The papers included address a wide variety of themes ranging from theories to applications of intelligent systems and computational intelligence area and provide a valuable resource for students and researchers in academia and industry alike.
Includes author index.
Keywords: Expert systems (Computer science) -- Congresses.; Artificial intelligence -- Congresses.; elektronické knihy; electronic books